Psychosocial interventions for bipolar disorder: a review of literature and introduction of the systematic treatment enhancement program. - Miklowitz, D; Otto, M (2007)
What is the evidence that psychosocial treatment adds to the efficacy of pharmacotherapy in forestalling episodes of bipolar disorder (BPD)? This article give s the rationale for including psychosocial intervention in the outpatient maintenance of BPD. Attention is placed on the three psychosocial modalities that have achieved empirical support in randomized trials: family psychoeducational treatment, cognitive-behavioral therapy, and interpersonal and social rhythm therapy. These three treatments are being contrasted with a psychosocial control condition in the context of the ongoing, multi-center Systematic Treatment Enhancement Program for Bipolar Disorder (STEP - BD). The objectives, design, and potential contributions of the STEP-BD study are explained. Future directions for the evaluation and dissemination of manual-based psychosocial interventions are discussed.